2016
DOI: 10.1080/00934690.2016.1194066
|View full text |Cite
|
Sign up to set email alerts
|

Bones, sex, and dolls: Solving a mystery in Central Africa and beyond

Abstract: Ethnographic parallels are used to explain the presence and significance of caprine or antelope metapodial bones principally in children's graves in Iron Age contexts in the Congo. Beyond Africa, in the Neolithic in France and Italy, but also during the Bronze Age in the Levant, the same mysterious bones have often been collected in similar contexts. It is likely that the natural shape of these bones led them to be seen as human figures and to be used as dolls. This is an example of how natural objects may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Such deep engagement with the forest may help explain the cache of 13 dwarf bovid metatarsals at Fukuchani. De Maret () demonstrated that ethnographically, bovid metapodials are commonly used as children's dolls and fertility symbols in central Africa and in numerous other contexts. Archaeologically, he notes that metapodials are associated with juvenile and some adult burials dating to the 9th–13th centuries CE in south‐eastern Congo.…”
Section: Discussionmentioning
confidence: 99%
“…Such deep engagement with the forest may help explain the cache of 13 dwarf bovid metatarsals at Fukuchani. De Maret () demonstrated that ethnographically, bovid metapodials are commonly used as children's dolls and fertility symbols in central Africa and in numerous other contexts. Archaeologically, he notes that metapodials are associated with juvenile and some adult burials dating to the 9th–13th centuries CE in south‐eastern Congo.…”
Section: Discussionmentioning
confidence: 99%
“…The study of past children continues to develop as a subfield of archaeology. Archaeological literature prior to Lillehammer's (1989) seminal paper included few references to children and their childhood and picked up the pace from the year 2000 (e.g., Baxter 2005aBaxter , 2005bBird and Bliege-Bird 2000;Bugarin 2005;de Maret 2016;Grimm 2000;Kamp 2001Kamp , 2015Sofaer Derevenski 2000). Despite this increasing interest in children of the past, however, we remain far from a routine consideration of their impact on the archaeological record and have consequently erased a significant proportion of past populations.…”
Section: Archaeology Of Children and Their Playmentioning
confidence: 99%